2006
DOI: 10.4067/s0716-078x2006000200012
|View full text |Cite
|
Sign up to set email alerts
|

Native and non-indigenous boring polychaetes in Chile: a threat to native and commercial mollusc species

Abstract: Native and non-indigenous boring polychaetes in Chile: a threat to native and commercial mollusc species ABSTRACTBoring polychaetes infesting the shells of aquacultured molluscs affect host fitness and cause serious economic problems for the aquaculture industry. In Chile, knowledge of the native and non-indigenous polychaete fauna associated with mollusc hosts is limited, in spite of the fact that numerous native and nonindigenous mollusc species are actively harvested. We present the first complete list of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(51 citation statements)
references
References 19 publications
1
45
0
5
Order By: Relevance
“…SatoOkoshi & Nomura 1990, Sato-Okoshi 1999, SatoOkoshi & Abe 2012, 2013. Additionally, all of the pest polydorids associated with cultured oysters in Australia (Walker 2014), 5 of the 6 species in Chile (Moreno et al 2006) and 3 of the most important pests in South Africa (Boonzaaier et al 2014, Simon 2015, Williams 2015 are alien.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…SatoOkoshi & Nomura 1990, Sato-Okoshi 1999, SatoOkoshi & Abe 2012, 2013. Additionally, all of the pest polydorids associated with cultured oysters in Australia (Walker 2014), 5 of the 6 species in Chile (Moreno et al 2006) and 3 of the most important pests in South Africa (Boonzaaier et al 2014, Simon 2015, Williams 2015 are alien.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, Haupt et al (2012) demonstrated that even after cleaning, oysters still harboured polydorid shellborers after translocation. Yet the records which confirm oysters and abalone as the vectors of transportation are limited; Polydora websteri and Boccardia proboscidea were transported from mainland USA to Hawai'i (Bailey-Brock & Ringwood 1982, BaileyBrock 2000, P. uncinata from Japan to Chile (Radashevsky & Olivares 2005), and probably P. websteri from Namibia to South Africa (Simon 2015, Williams 2015, while the sabellid Terebrasabella heterouncinata was transported from South Africa to California and further (Culver et al 1997, Moreno et al 2006. In some instances aquaculture may not have been the vector of introduction of a pest to a new region, but is responsible for its spread within its introduced range (e.g.…”
Section: Movement Of Pests With Molluscs In Aquaculturementioning
confidence: 99%
See 3 more Smart Citations